2020
DOI: 10.1007/s00261-020-02865-0
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of burden and management of renal calculi from whole kidney radiomics: a multicenter study

Abstract: Purpose To assess if autosegmentation-assisted radiomics can predict disease burden, hydronephrosis, and treatment strategies in patients with renal calculi. Methods The local ethical committee-approved, retrospective study included 202 adult patients (mean age: 53 ± 17 years; male: 103; female: 99) who underwent clinically indicated, non-contrast abdomen-pelvis CT for suspected or known renal calculi. All CT examinations were reviewed to determine the presence (n = 123 patients) or absence (n = 79) of renal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Radiomics analysis allows for the quantitative analysis of a wide range of morphologic and physiologic properties of selected tissues, including shape and histogram‐based and textural features 11,12 . Radiomics has been widely applied in the analysis of various organs and tissues such as the liver, breast, kidney, brain, and lung 13–16 . Therefore, we also evaluated the predictive value of features extracted from ultrasound images to investigate the possibility of integrating radiomics into the prediction model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiomics analysis allows for the quantitative analysis of a wide range of morphologic and physiologic properties of selected tissues, including shape and histogram‐based and textural features 11,12 . Radiomics has been widely applied in the analysis of various organs and tissues such as the liver, breast, kidney, brain, and lung 13–16 . Therefore, we also evaluated the predictive value of features extracted from ultrasound images to investigate the possibility of integrating radiomics into the prediction model.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Radiomics has been widely applied in the analysis of various organs and tissues such as the liver, breast, kidney, brain, and lung. [13][14][15][16] Therefore, we also evaluated the predictive value of features extracted from ultrasound images to investigate the possibility of integrating radiomics into the prediction model.…”
Section: Introductionmentioning
confidence: 99%
“…Second, manual set for ROI was performed by students and radiologists reading the DWI images. On CT or MRI, automatic segmentation based on deep learning has been successfully established with equivalent accuracy to expert segmentation in kidneys [5,17,18]. Due to the small volume in children's kidneys, it is difficult to tell the kidneys apart from other organs in the body which may have comparable intensity, especially in CAKUT.…”
Section: Discussionmentioning
confidence: 99%
“…19 Homayounieh et al have demonstrated that stone radiomics features (most notably stone volume) are highly predictive of future hydronephrosis, future stone burden, and invasive treatment. 22 Relatively few works have been published that tackle the challenge of computer-aided detection of kidney stones in CT. Lee et al used texture-and intensity-based features to train an artificial neural network to distinguish kidney stones from vascular calcifications. 23 Liu et al segmented the kidneys and then used total-variation flow denoising followed by the maximal stable extremal regions method to segment stones.…”
Section: Introductionmentioning
confidence: 99%
“…Homayounieh et al. have demonstrated that stone radiomics features (most notably stone volume) are highly predictive of future hydronephrosis, future stone burden, and invasive treatment 22 …”
Section: Introductionmentioning
confidence: 99%